Frequency and character of low back pain in Moscow outpatients. Report I - S F Erdes; T V Dubinina; E A Galushko (Научно-практическая ревматология, 2007)
Objective. To define frequency and character of low back pain (LBP) in Moscow outpatients. Material and methods. 1300 pts aged 18 to 50 years actively seeking medical care in ambulance №17 of Moscow South Administrative Region were examined during one month with a questionnaire developed in the Institute of Rheumatology of RAMS. Results. LBP is a frequent reason of visits to a doctor in outpatient practice. Majority of such pts had acute and subacute pain. Cases with moderate or severe pain were predominant. LBP is a frequent cause of disability.